Seasonal species diversity, dominance and density of diatomic phytoplankton in Tigris River, Baghdad Province, Iraq - Bashar Tareq Al-Shandah; Trifa Kamal Jalal; Muhanned Remzi Nashaat (Caspian Journal of Environmental Sciences)
Phytoplankton plays a key role in solving some environmental problems, studying photosynthesis, understanding aquatic ecosystems and the production of useful substances. In the present study, monthly analysis of diatomic phytoplankton communities as well as diatomic algae distribution, total count, annual density, density percentage, diversity and dominance of different species were carried out to assess the phytoplankton structure of Tigris River, a major source of fresh water in Iraq. Water samples were collected on a monthly basis from four sites of the river in the Iraqi Capital, Baghdad. The study period was one year from January to the end of December 2021.  In this study, 125, 130, 123, and 141 fresh water algal species belonging to class Bacillariophyceae were identified reporting from stations 1, 2, 3 and 4 respectively. In this study, Cyclotella ocellata was the most dominant in all sampling stations. The highest total annual density of phytoplankton during the study period was at  St. 3 (34416 ind ×103 L-1), followed by (34306.85 ind × 103 L-1) at  St. 1, and (33335.8 ind × 103 L-1) at  St. 4, finally, the lowest at  St. 2 (29121.5 ind × 103 L-1). Seasonal phytoplankton diversity was investigated based on Shannon Diversity Index (H) exhibiting the highest diversity index in summer (3.041), followed by winter (2.606), spring (2.22) and the lowest in autumn (1.355). Eventually, the study area within Tigris River is classified as moderate mostly based on Shannon Diversity Index for Water quality classification. Finally, seasonal diatomic phytoplankton dominance was investigated based on Simpson's Index (D) exhibiting the highest dominance index in autumn (0.549), followed by spring (0.35), winter (0.23) while the lowest in summer (0.12). These last results confirmed the inverse relationship between Simpson's Index for the dominance and Shannon diversity index for the biodiversity.